Raman Spectroscopy for The Determination of Relative Crystallinity of Carbon Fibers - Indra Neel Pulidindi (International Journal of Crystalline Materials, 2024)
Analogous to X-ray diffraction technique, the light scattering technique discovered by Sir CV Raman has great potential in quantifying the crystallinity of new materials, like the highly crystalline pitch based carbon fibers (NX90 and NX100). For comparison the Raman spectra of polyacrylonitrile based carbon fibers (T700SC) were also recorded. From the Raman spectral analysis, it was found that the pitch based carbon fibers exhibit far far higher degree of crystallinity compared to PAN based carbon fibers. In fact, PAN based fibers have carbon micro structure analogous to the amorphous activated carbon with the regular disorder band (D band) and the graphitic band (G band). In sharp contrast to the PAN based carbon fibers, the pitch based fibers showed polycrystalline graphitic structure. In the Raman spectra of the pitch based carbon fibers, the signal at ~ 1348 – 1358 cm-1 should not be mistaken with the regular disordered carbon structure found in amorphous carbon materials and this band should not be attributed to the regular D band. Rather, this band located in the range of ~ 1348 – 1358 cm-1 corresponds to the crystalline graphitic structure that arise due to the well crystallized graphite with smaller crystallite size (~ 29 nm). As the D band itself is absent in the pitch based fibers, the conventional Raman intensity ratio (R = 𝐼𝐷𝐼𝑅) corresponding to the degree of graphitization or degree of crystallization cannot be used as a measure. Rather a revised Raman intensity ratio, given by, R_(NX90/NX100)= 〖(I_CG+I_G)〗_NX90/((〖I_CG+I_G)〗_NX100 ), where CG (~ 1348 – 1358 cm-1) and G (1575 – 1584 cm-1) corresponds to crystalline graphite and graphite respectively, provides an accurate quantitative measure of the relative cyrstallinity of highly crystalline materials like NX90 and NX100 where the disordered structure is almost absent. Using the revised Raman intensity ratio, it was found that the degree of crystallinity of NX90 is 2.3 times higher than that of NX100. Thus Raman spectroscopy forms a quantitative analytical tool for evaluating the relative crystallinity of carbon fibers.
Keywords: Carbon fibers; Raman Spectroscopy; Revised Raman intensity ratio; crystallinity; graphitization; pitch; polyacrylonitrile